Teachers’ Way in Scoring Students Speaking Performance at School Parepare - Zam-zam Adam; Zulfah Fakhruddin; Ambo Dalle; Abdul Haris Sunubi; Arqam (International Journal of Health, Economics, and Social Sciences (IJHESS), 2024)
This result discusses how teachers give scores to students' speaking performances. In this case, the teacher who is the respondent has a different main assessment in giving scores to students' speaking performance. and each has its own challenges with 3 types of scoring assessments, namely holistic, analytical and using rubrics. The research method used is qualitative, data is collected through observation, in-depth interviews and also documentation. The subjects of this research consisted of several English teachers in Parepare. The results of this study indicate that teachers use various assessment theories in their evaluation practices. These theories include holistic, analytical, and use of rubrics, with different main assessment points.